Supply Chain Management Implementation on Snacks Production Process - Sahara Syarifatul Choeriyah; Eko Budi Setiawan (IJNMT (International Journal of New Media Technology), 2018)
PQR’s company is a company that located in Citeureup Tasikmalaya. The company is engaged in the production of snacks such as mie lidi. The production strategy that used by this company is a make to stock. The company organizes activities from upstream to downstream. Activities that occur in the upstream is to procure raw materials to suppliers by purchasing department. However, some problem was found when the purchasing department has difficulty determining the amount of raw material for the procurement process. This is due to uncertain demand from distributors. While the activities in downstream is sending the product to distributor by shipping department. Some problem that occurs in the downstream were shipping department has difficulty to make schedule product shipments because there was a delay in the product delivery process. All problem occurs because there is no system that can manage supply chain information. So, the implementation of supply chain management by using the forecasting method of single moving average and calculation of sale limits of raw material and product inventory using safety stock method, it was expected to provide a solution to this problem.